Multilayer Integrated Film Bulk Acoustic Resonators - Zhang, Yafei; Chen, Da.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Multilayer Integrated Film Bulk Acoustic Resonators mainly introduces the theory, design, fabrication technology and application of a recently developed new type of device, multilayer integrated film bulk acoustic resonators, at the micro and nano scale involving microelectronic devices, integrated circuits, optical devices, sensors and actuators, acoustic resonators, micro-nano manufacturing, multilayer integration, device theory and design principles, etc. These devices can work at very high frequencies by using the newly developed theory, design, and fabrication technology of nano and micro devices. Readers in fields of IC, electronic devices, sensors, materials, and films etc. will benefit from this book by learning the detailed fundamentals and potential applications of these advanced devices. Prof. Yafei Zhang is the director of the Ministry of Education$1 (Bs Key Laboratory for Thin Films and Microfabrication Technology, PRC; Dr. Da Chen was a PhD student in Prof. Yafei Zhang$1 (Bs research group.s
Introduction -- Propagation of Acoustic Wave in Crystals -- The Theory of FBAR -- The Sputtering Deposition and Etching of AlN Film -- The Membrane Structured FBAR -- Solidly Mounted Acoustic Resonator -- The Application of FBAR in RF Filters -- The FBAR Excited by Lateral Filed -- High Sensitive Sensors Based on FBAR.
Keywords: Engineering; Surfaces (Physics).; Engineering; Nanotechnology and Microengineering; Surfaces and Interfaces, Thin Films; Solid State Physics